Thermal characterization of non-functionalized low content graphene nanoplatelets (GNP) added nylon 66 polymer - Abd Manaf, Mohd Edeerozey; Shueb, Mohammed Iqbal; Mohamed, Mahathir; Umar, Khairil Nor Kamal; Mohamad, Noraiham; Abd Razak, Jeeferie; Abdullah Sani, Nurhernida (Penerbit Akademia Baru, 2022)
Thermal behaviour of graphene nanoplatelets (GNP) reinforced nylon 66 nanocomposites were investigated using differential calorimetric scanning (DSC), thermogravimetric analyzer (TGA) and dynamic mechanical analysis (DMA). The influence of low content GNP on thermal properties of GNP/nylon 66 nanocomposites was studied for low GNP content (0.3, 0.5 and 1.0 wt%). DSC results indicate that addition of GNP increases crystallization temperature and degree of crystallinity of the nanocomposites. Thermal stability and mass loss were studied through TGA analysis. The results show that thermal stability and weight loss of GNP/nylon 66 nanocomposites slightly improve with the GNP addition with an increase in the onset of degradation temperature as much as 10 °C. DMA analysis shows that GNP in the nylon 66 matrix act similar to plasticizer; it decreases the storage modulus and glass transition temperatures of the nanocomposites. GNP addition also reduces tan δ indicating an improvement in the damping property of the nanocomposites. Overall, this study concludes that a minimal amount of 0.3 wt% of GNP is effective in improving the thermal properties of nylon 66 composites.